PENGARUH PENERAPANSISTEM PENGENDALIAN INTERN KAS, IMPLEMENTASI GOOD CORPORATE GOVERNANCE DAN KETAATAN ATURAN AKUNTANSI TERHADAP FRAUD PADA PERUSAHAAN BUMN DI KOTA PEKANBARU - Raja Reno Setiawan; Nur Azlina; Julita ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this study was to Test back relationship with the Treasury Internal Control System Implementation of Good Corporate Governance Fraud.hubungan with Fraud and reexamine relations Accounting Rules Compliance with Fraud. Selected population in this study is the State Owned Enterprises located in the city of Pekanbaru many as 24 state-owned enterprises . The sample in this study as many as 49. The analysis of research on the use is use multiple linear regression equation with SPSS (Statistical Product and Service Solution).The research hypothesis first hypothesis suggests that the Internal Control of Cash a negative effect on Fraud. The second hypothesis suggests that GCG implementation negatively affect Fraud. Three hypotheses suggests that adherence Accounting Rules negative effect on Fraud. 0375 R2sebesar calculation results. Thus variables can explain the variable implementation of good corporate governance, internal control and compliance time Cash accounting rules take effect at 37.5%. The rest was influenced by other variables that are not observed in this study, such as individual morality, organizational ethics, justice organizations and others.Keywords : Cash Internal Control System, Implementation of Good Corporate Governance, Compliance Rules Accounting and Fraud